Physical performance, body composition and body balance in relation to national ranking positions in young polish tennis players - Karnia, M.; Garsztka, T.; Rynkiewicz, M.; Rynkiewicz, T.; Zurek, P.; Luszczyk, M.; Sledziewska, E.; Ziemann, E. (Baltic Journal of Health and Physical Activity, 2010)
Background: Tennis is characterized with short and intermittent efforts of an altering intensity and time where numerous factors determine the achieved success. Some of them include human's morphological body build, motor abilities and efficiency of the energetic systems. Both motor abilities and physical capacity appear to be particularly significant due to the unpredictable time and weather situation of the tournaments. The purpose of this study was to determine the relationship between body composition, aerobic capacity and the balance in young tennis players at rest and during fatigue triggered by an endurance test. Moreover, we tried to find the correlation between the tennis ranking position and the balance.